Mapeo de las competencias clave para la gerencia de proyectos. Caso proyectos del sector hidrocarburos en Colombia (2016)
An essential feature of the professionals who are selected and evaluated for leadership roles is the skills profile; area where a pioneering author is David C. McClelland (1973) who against the limited success of the selection process focused solely on intelligence tests and schooling, proposed encouraging the design and implementation of proficiency tests; and a position where good performance depends, among other things, specialized knowledge, skills and talent manager.    As generic activity management and project management as a specific work demands mastery of a core set of skills that Lyle M. Spencer, Jr. and Signe M. Spencer (1993) described a practical dictionary in which recently relied Raquel Manuel Centeno and Serafin (2006) to define a competency model for the training of project managers. Referring study Centeno and Serafin the need to specify the essential skills for good performance in project management in scenarios of uncertainty, such as those faced by those who are part of the value chain of oil companies (Avellaneda was raised Cusaría, 2005). The research developed in the form of degree work to obtain the title of magister which is presented in this report, sought to establish the core competencies for a good performance in project management Colombian hydrocarbon sector. To achieve this objective designed an inductive inquiry it was developed with qualitative data analysis where the analysis units were key competences for project management. The criteria were defined and applied validity logical consistency and similarity. The main frames of reference for generic management competencies were the Ministry of Education ((MEN, 2008), the Project Management Institute (PMI, 2013) and IPMA). Additionally, competency profiles defined by some of the most representative companies in the sector analyzed were reviewed.   Work degree is articulated to the research in project management that supports the Master in Development and Integrated Project Management (MDYGIP) of the Colombian School of Engineering Julio Garavito and provides advanced training in management issues and prescriptive consolidation of research on issues of organization and management. The document is divided into 7 chapters. In the first chapter the problem definition, divided into the background, the formulation and description shown. In the second chapter Labour justification of the thesis is presented in the third chapter are the general and specific objective. The fourth chapter is the framework document reference which is divided into competencies in higher education, key competencies, concept and description, list of references on professional competence, list of references on skills for management, and finally in the reference list in the competencies of companies in the hydrocarbon sector. The fifth chapter the methodological design layout is described to address the question of the project, where the criteria of validity and reliability, population and study sample, and the case study of business managers in the hydrocarbon sector are analyzed, the sixth chapter shows the results and discussion and finally the seventh chapter with conclusions and recommendations Labour grade.